Pendapat Mahasiswa tentang Fleksibilitas Kurikulum Suplemen 2000 di Jurusan PDU FIS UNY - Endang Mulyani (Universitas Negeri Yogyakarta, 2004)
This study examines the PDU students perception of 2000 curriculum flexibility. The results of this study show that 98% of respondents agree with the implementation of flexible curriculum, majority of flexibility interested is additional competency to teach to other study programs. This curriculum has two advantages, namely: students can receive more than one competency, time needed to finish study and receive two diplomas is shorter than other universities. On the other hand, this curriculum has disadvantages such as: students have to spend much more money, it is need longer time to finish study and quality of graduates is questionable.